A Review on Synthesis, Optimization, Mechanism, Characterization, and Antibacterial Application of Silver Nanoparticles Synthesized from Plants - Sunday Adewale Akintelu; Yao Bo; Aderonke Similoluwa Folorunso (Journal of Chemistry)
Developments in nanotechnology and natural product research toward the search for novel antibacterial agents have drawn the interest of many scientists to the synthesis of silver nanoparticles (AgNPs) from natural product (especially plants) due to its numerous benefits over other methods of synthesis such as been easy, economical, convenient, and environmental friendly. Aside from the aforementioned advantages, the synthesis of AgNPs from medicinal plant has been reported as the best approach of synthesizing AgNPs with great biological activities due to the numerous biomolecules found in plants. Recently, the number of researches toward the improvement of the yield, morphological properties, analytical techniques, and the development of optimal conditions and exact mechanism for synthesizing AgNPs from plants have been increasing tremendously. In this review, we present a comprehensive report on the recent development in the synthesis, optimization conditions, mechanism, and characterization techniques of AgNPs synthesized from plant extracts. Furthermore, a thorough discussion on the recent advances in the application of AgNPs synthesized from plant as therapeutic agent against bacterial infections was made.